Description of Knowledge, Attitude, and Act Girls Teenager on Breast Self Examination (BSE) at Budi Murni 1 Chatolic Senior High School Medan in 2014 - maria pane; Lita Sri Andayani; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Breast self examination (BSE) is a way to do a woman to detect early abnormalities in the breast. Generally can be done by girls from the age of productive and has experienced changes the physical characteristics of primary and secondary. BSE goal is to determine whether there is abnormality such as breast cancer. The purpose of this study was to determine the internal factors, external factors, knowledge, attitudes and actions girls about breast self-examination (BSE). Type of research is descriptive research. In this study the number of population is all students of class XII SMA Katolik Budi Murni 1Medan as many as 200 people and sampled as many as 62 people. Sampling techniques using simple random sampling technique. Data collected by using a questionnaire. The data were analyzed using descriptive statistics. Based on the analysis of the study found adolescent knowledge about BSE were in the category of less than 61.3%. Student attitudes regarding BSE is in good enough category of 54.8%. And student action against BSE no middle category (74.2%). From these results it is expected that the school, parents, and caregivers around can play an active role in providing information about methods of early detection of breast self-examination and breast cancer in the students.